Ethical issues in the Abraham narrative - Davies, Eryl W. (Library of Hebrew bible/Old Testament studies, 2025)
"Eryl W. Davies enhances understanding of the ethical issues embedded in the stories concerning Abraham in Genesis 12-25. He focuses on the ethics of deception in Gen. 12:10-20 and 20:1-18 and the 'dark side' of the character of God, as revealed in stories such as the binding of Isaac in Gen. 22, while also considering how the writings of philosophers such as Kant, Kierkegaard and Habermas illuminate aspects of the biblical stories"--